2012
DOI: 10.1186/2191-5040-1-2
|View full text |Cite
|
Sign up to set email alerts
|

Short- and long-term evacuation of people and livestock during a volcanic crisis: lessons from the 1991 eruption of Volcán Hudson, Chile

Abstract: Human and livestock evacuation during volcanic crises is an essential component of volcanic risk management. This study investigates the evacuation of human and livestock populations from areas impacted by ashfall from the 1991 Hudson eruption, Patagonia. The eruption was one of the largest in the 20 th century resulting in significant impacts on rural communities in affected areas, including the evacuation of people and livestock. In the short-term (<3 months), evacuation of people from farms and rural towns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 28 publications
0
27
0
1
Order By: Relevance
“…Similarly to the CC eruption, a massive loss of sheep (1 million) and cattle (about a thousand) in Argentina and Chile was estimated, due to burial of vegetation from tephra, water contamination and animal poor health conditions. As in the case of CC eruption, Wilson et al (2010Wilson et al ( , 2012) also reported animals with gastrointestinal affections, teeth abrasion, blindness, immobilization and dehydration. Impact on vegetation varied according to the thickness of the tephra deposit.…”
Section: The 1991 Hudson Eruptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly to the CC eruption, a massive loss of sheep (1 million) and cattle (about a thousand) in Argentina and Chile was estimated, due to burial of vegetation from tephra, water contamination and animal poor health conditions. As in the case of CC eruption, Wilson et al (2010Wilson et al ( , 2012) also reported animals with gastrointestinal affections, teeth abrasion, blindness, immobilization and dehydration. Impact on vegetation varied according to the thickness of the tephra deposit.…”
Section: The 1991 Hudson Eruptionmentioning
confidence: 99%
“…The impact of this eruption, very similar to that described for the CC eruption, included big economic losses in Patagonia, mainly from the impact on livestock and crops, air traffic disruption and water contamination. As in CC, Wilson et al (2010Wilson et al ( , 2012) also reported interruptions and disruptions in electricity and water supply, accumulation of pumice in lakes over a long period of time, abrasion and weathering of machinery and electrical devices. An important psychological-social impact in the population was also recorded, combined with the abandonment from farms and towns (in Puerto Ibañez, Chile, the spontaneous evacuation of people was gradual, reporting a decrease of 30 % from a starting population of 4000).…”
Section: The 1991 Hudson Eruptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although active volcanoes can pose threats to the populations living around them, fertile soils, equable climates and increasingly the livelihoods afforded through tourism can exert a strong pull (Tobin & Whiteford 2002;Kelman & Mather 2008;Wilson et al 2012). Coupled with human attachment to place and community (Dibben & Chester 1999), this means that people may have compelling reasons to live with the risks associated with volcanoes.…”
Section: Introductionmentioning
confidence: 99%
“…Model outputs include the mass of tephra accumulation, in units of kg m -2 , and a binned distribution of particle sizes calculated as weight percent of the total mass at specific locations around the erupting volcano. The mass per unit area is often directly used in hazard forecasts, since mass loading by tephra affects infrastructure resilience (Wilson et al 2012). Small particle sizes directly affect air quality (due to resuspension of particles in the atmosphere); they also increase an area's susceptibility to flooding (tephra can dramatically impact infiltration rates of meteoric water into the ground; Blong 1984).…”
Section: Tephra2mentioning
confidence: 99%